Cytoskeleton - Structure, Dynamics, Function and Disease 2017
DOI: 10.5772/66865
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton Rearrangements during the Execution Phase of Apoptosis

Abstract: Apoptosis is a regulated energy-dependent process for the elimination of unnecessary or damaged cells during embryonic development, tissue homeostasis and many pathological conditions. Apoptosis is characterized by specific morphological and biochemical features in which caspase activation has a pivotal role. During apoptosis, cells undergo characteristic morphological reorganizations in which the cytoskeleton participates actively. Traditionally, this cytoskeleton rearrangement has been assigned mainly to act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, when comparing the elasticity dynamics in different modes of RCD, clear differences could be distinguished ( Figure 3 B). Most likely the fast decrease in elasticity of cells undergoing apoptosis can be explained through an active reorganization and depolymerization of the cytoskeleton by protein activation/inhibition during apoptosis (such as MLCK, ROCKs, executioner caspases), as was previously shown ( Doncel et al., 2017 ; Oropesa-Ávila et al., 2017 ). In this work, it has been suggested that, owing to the absence of any active reorganization in both necroptosis and ferroptosis, the elasticity decrease is more gradual.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, when comparing the elasticity dynamics in different modes of RCD, clear differences could be distinguished ( Figure 3 B). Most likely the fast decrease in elasticity of cells undergoing apoptosis can be explained through an active reorganization and depolymerization of the cytoskeleton by protein activation/inhibition during apoptosis (such as MLCK, ROCKs, executioner caspases), as was previously shown ( Doncel et al., 2017 ; Oropesa-Ávila et al., 2017 ). In this work, it has been suggested that, owing to the absence of any active reorganization in both necroptosis and ferroptosis, the elasticity decrease is more gradual.…”
Section: Discussionmentioning
confidence: 64%
“…The blue fluorescence of DAPI permits the visualization of nuclear fragments and condensed nuclei, with the advantages of using it being DNA selectivity and enhanced cell permeability [ 20 ]. Moreover, the cell’s cytoskeleton is formed of actin filaments, microtubules, and intermediate filaments, constituents which are important to ensure cell motility, plasma integrity, characteristic cell morphology, and for allowing cellular transport [ 37 ]. However, one of the hallmarks of cancer is exactly the increased motility of cells, which allows the invasion of adjacent healthy tissues and metastasis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 The BFA dc DEP-EMF’s influence on diamagnetic anisotropy via membrane potential, chloride ion channel modulation and significantly increased transcription (Figure 4) 14 may possibly offer more available ATP (G-Actin/ATP complexes—thereby increasing critical concentrations high enough to affect both the plus and minus end of the actin [unbranched] filaments and subsequent reorganization/elongation of microtubules) to be used by the cell and facilitate cytoskeletal reorganizations (round apoptotic microtubule spikes) for the round apoptosis in these MDA-MB-231 cells (Figure 1). 20…”
Section: Discussionmentioning
confidence: 99%